Five animal phyla in glacier ice reveal unprecedented biodiversity in New Zealand's Southern Alps - Daniel H. Shain (Nature Portfolio, 2021)
Abstract Glacier ice is an extreme environment in which most animals cannot survive. Here we report the colonization of high elevation, climate-threatened glaciers along New Zealand’s southwestern coast by species of Arthropoda, Nematoda, Platyhelminthes, Rotifera and Tardigrada. Based on DNA barcoding and haplotype-inferred evidence for deep genetic variability, at least 12 undescribed species are reported, some of which have persisted in this niche habitat throughout the Pleistocene. These findings identify not only an atypical biodiversity hotspot but also highlight the adaptive plasticity of microinvertebrate Animalia.